Children picture book: Fatah & Si Kuman/ Aqilah Nadhira Athasania - Athasania, Aqilah Nadhira (2022)
Fatah & Si Kuman is a picture story book for children about the importance of washing hands before eating, using simple explanations and visual illustrations adapted for children, cute and adorable.